ASP-Core-2 Input Language Format. Issue 2 (20th March 2020) - CALIMERI, FRANCESCO; FABER, WOLFGANG; GEBSER, MARTIN; IANNI, GIOVAMBATTISTA; KAMINSKI, ROLAND; KRENNWALLNER, THOMAS; LEONE, NICOLA; MARATEA, MARCO; RICCA, FRANCESCO; SCHAUB, TORSTEN
Abstract: Standardization of solver input languages has been a main driver for the growth of several areas within knowledge representation and reasoning, fostering the exploitation in actual applications. In this document, we present the ASP-CORE-2 standard input language for Answer Set Programming, which has been adopted in ASP Competition events since 2013.